Pembukaan Rahasia Bank dalam Perkara Tindak Pidana Pencucian Uang - Burham Pranawa (Fakultas Hukum Universitas Boyolali, 2023)
The perpetrators of money laundering crimes use bank facilities to hide assets from the proceeds of their crimes. The bank was chosen as a means to hide their assets because the bank has rules regarding bank secrecy which gives the account owner the right to keep the identity and value of deposits in the bank confidential. The purpose of this study is to discuss the concept of money laundering and the process of disclosing bank secrets to perpetrators of money laundering crimes. The research method used is a normative/doctrinal approach, descriptive research type, secondary data sources, data collection methods using literature and documentation, qualitative normative data analysis methods and deductive conclusions drawn. The concept of money laundering is clearly regulated in Law Number 8 of 2010 concerning the prevention and eradication of money laundering which regulates the meaning of money laundering, the subjects of money laundering offenders, elements of money laundering crimes and sanctions against perpetrators of money laundering crimes. The process of disclosing bank secrets for perpetrators of money laundering crimes can be carried out by officials who have the authority to disclose.